THE INFLUENCE OF SELF-ESTEEM AND TOEFL PBT SCORE TOWARD SPEAKING 4 ACHIEVEMENT OF THE EVEN SEMESTER OF ENGLISH EDUCATION STUDY PROGRAM FKIP MUHAMMADIYAH UNIVERSITY OF PALEMBANG - S, Sinta (Universitas Muhammadiyah Palembang, 2018)
This study investigated whether or not self-esteem and TOEFL scores can influence students’ speaking 4 achievement. The population of this study was fourth, sixth, and eighth semester students of English Education Study Program, Muhammadiyah University of Palembang in academic year 2012/2013. The data were collected by documentation for speaking 4 achievement and TOEFL scores, and the data were collected by using questionaire for Self-esteem. The data were analyzed by using F-test and regression analysis. There was significant Influence between Self-esteem and speaking 4 score (r=0.206>0.05), TOEFL scores and speaking 4 score (r=0.123>0.05), Self-esteem and TOEFL score on speaking 4 score (r=.0.235>0.05). it was assumed that a fairly correlation between sudents’ Self-esteem and students’ TOEFL scores on their speaking 4 achievement was caused from the internal factor of personal learner as a speaker or it might be untruthfullness of the students’ Self-esteem when filling out the questionnaire and the limitation of their second language foundation and their reluctancy in doing more speaking.